La conversation latine dans les classes inférieures - Poissinger, A. (S.l. : s.n., 1908)
Bibliotheek Camille Huysmans
Dedicator: Poissinger, A., dedicatee: Descamps, Edouard
Frans
Brochure
Keywords: taal; onderwijs